The role of Ca²⁺ and cAMP in GnRH-stimulated LH release - Wakefield, Ian Kurt (Division of Chemical Pathology, 2018)
In this thesis a detailed study of the kinetics of GnRH-stimulated LH release was made. GnRH stimulated LH release in a biphasic manner. During the first 3 minutes of stimulation, there was a transient spike phase of release followed by plateau phase of lower amplitude. Both phases of release are largely dependent on extracellular Ca²⁺. The spike phase of release is dependent on Ca²⁺ entry via a receptor-operated Ca²⁺ channel (ROCC) (about 90%) and on the mobilization of intracellular Ca²⁺ stores. The role of ROCC were examined by using ruthenium red which inhibits both ROCC and voltage-sensitive Ca²⁺ channels (VSCC). VSCC are not involved in the spike phase of GnRH-stimulated LH release since D600 and nifedipine, inhibitors of VSCC, have no effect on the spike phase. The plateau phase of release is dependent on Ca²⁺ entry via VSCC (about 50%) and ROCC (about 50%). Forskolin, an activator of adenylate cyclase, was used to investigate the role of cAMP in LH release. Forskolin stimulated an increase in both LH release and cellular cAMP levels. GnRH was also able to elevate the cellular CAMP concentration. GnRH interacted synergistically with forskolin to stimulate LH release. The synergism between GnRH and forskolin was not due to an interaction at (1) the GnRH receptor, (2) the level of intracellular Ca²⁺ mobilization, or (3) inositol phosphate metabolism. However, forskolin was able to synergistically interact with secretagogues that increase the cytosolic Ca²⁺ concentration and activators of protein kinase C. This suggested that forskolin was interacting with GnRH at a site distal to the activation of the Ca²⁺ second messenger system and protein kinase C. The data suggest that the initial response to GnRH is largely Ca²⁺-dependent and that other second messengers, if active, play a minor role. cAMP is thought to play a modulatory role and may be involved in the maintenance of secretion.